Język polityka, polityka w języku/Polityka na językach. Rozważania na temat werbalnych form kontaktu z wyborcami polskich działaczy politycznych (analiza internetowych wydań środków społecznego przekazu u schyłku pierwszego dziesięciolecia XXI w.) - Wiśniewska, Paulina (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
Appropriately selected and uttered words are a significant point of concern for the creators of a politician’s image, primarily the image of actors on the political stage. Theoretically, a politician is obligated to use simple, clear, cohesive, logical – and first and foremost – correct language. Aword uttered by a politician should stimulate activity and not be content with itself. Polish reality, however, is characterized by the aggressive language of parliamentary debates or unsophisticated, or plainly offensive, expressions directed at the political opposition.